Mineral Binder Based on Waste of Other Productions - Chernyak, Lev (European Journal of Applied Sciences, 2022)
In this article possibility of a complex solution of the tasks of ecology and chemical technology of silicates in the preparation of mineral binder material on the basis of rich-tonnage inputs of other varieties was studied. By means of the computer program "Clinker" new compositions of raw materials based on the system of chalk - rice husk - paper scope with a total content of 64-71 wt.% of these wastes are determined. The method of X-ray phase analysis shows the peculiarities of the formation of the phase composition during firing of the developed mixtures with a maximum temperature of 1400 ºC. Standardized technological tests were performed and differences in the properties of the mineral binder were determined when varying the quantitative ratio of components in the composition of the initial mixture.